Fenton-like catalytic system and application thereof in degradation of acetaminophen
By using a nano-scale MXene catalyst coupled with H2O2, the Fenton-like catalytic system is solved, and the problem of difficulty in degrading acetaminophen is achieved, efficient, economical and environmentally friendly sewage treatment is achieved, and the treatment needs of acetaminophen sewage is met.
Patent Information
- Application Number
- CN202411716862.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-27
AI Technical Summary
Traditional wastewater treatment methods are difficult to completely degrade acetaminophen, and Fenton technology has problems such as low H2O2 utilization rate, narrow pH application range, and large amount of iron-based sludge, making it difficult to meet the treatment requirements of acetaminophen in sewage.
MXene with nanoscale thickness and submicron or micron lateral dimensions are used as catalysts to couple H2O2 to form a Fenton-like catalytic system, with high H2O2 utilization, wide pH range, low energy consumption and low cost.
In light or light, the Fenton-like catalytic system can effectively degrade acetaminophen, improve the utilization rate of H2O2, expand the scope of pH application, reduce energy consumption and cost, and meet the treatment requirements of acetaminophen-containing wastewater.
Smart Images

Figure CN119551798A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of water treatment technology, and in particular to a Fenton-like catalytic system and its application in the degradation of acetaminophen. Background Art
[0002] In recent years, acetaminophen (ACTP) has been widely used as a drug that can effectively treat fever, inflammation, pain and other diseases. Due to the large amount of ACTP released into the aquatic environment during the production process and human metabolism, it is widely present in the global water environment, becoming one of the water pollution problems faced by all mankind, causing great harm to human health and the ecological environment. Traditional wastewater treatment methods (such as biological methods, physical adsorption, etc.) are difficult to completely degrade ACTP. Therefore, an efficient, safe, environmentally friendly and economical ACTP degradation treatment technology is urgently needed.
[0003] Fenton technology is one of the fastest, most efficient and environmentally friendly advanced oxidation processes for treating wastewater. It can react at room temperature and pressure and has the advantages of fast reaction rate, good degradation effect and simple operation. However, it has problems such as low H2O2 utilization rate, narrow pH application range and large amount of iron-based sludge, which restrict the development of Fenton technology and make it difficult to meet the treatment requirements of acetaminophen in wastewater. Summary of the invention
[0004] Based on this, the main purpose of this application is to provide a Fenton-like catalytic system, which uses MXene with nanometer-level thickness and submicron or micron-level lateral dimensions as a catalyst, coupled with H2O2, and has the advantages of high H2O2 utilization, wide pH application range, low energy consumption, and low cost. It can achieve effective degradation of acetaminophen in the presence or absence of light, and meet the treatment requirements of wastewater containing acetaminophen.
[0005] In a first aspect of the present application, a Fenton-like catalytic system is provided, comprising MXene and H2O2.
[0006] In some embodiments, the chemical formula of the MXene is M n+1 X n T x ; wherein n=1-3, M is selected from Ti, V, Mo, Sc, Zr, W, Cr, Ta, Nb or Hf; X is C or N; T x Selected from -OH, -F, -Cl or -O.
[0007] In some embodiments, the MXene is Ti3C2T x ; The Ti3C2T x The preparation method comprises:
[0008] Mixing lithium fluoride with the first hydrochloric acid solution to prepare a mixed solution;
[0009] The MAX phase material is added to the mixed solution, an etching reaction is performed, a first centrifugation is performed, the solid phase is washed with a second hydrochloric acid solution, and dried to prepare the Ti3C2T x .
[0010] In some embodiments, the molar concentration of the first hydrochloric acid solution is 6-12 mol / L;
[0011] and / or the mass volume ratio of the lithium fluoride to the first hydrochloric acid solution is 1 g: (10-30) mL;
[0012] and / or the mass ratio of the MAX phase material to the lithium fluoride is (0.3-1):1;
[0013] And / or the molar concentration of the second hydrochloric acid solution is 1-3 mol / L.
[0014] In some embodiments, the conditions for mixing lithium fluoride with the first hydrochloric acid solution include: stirring at a speed of 300-800 rpm for 60-90 min;
[0015] And / or the etching reaction conditions include: 25-40° C. reaction time for 24-72 hours.
[0016] In some embodiments, the drying step further includes an intercalation stripping step; the intercalation stripping step includes:
[0017] The dried solid phase is dispersed in the intercalant, sheared and stripped, and subjected to a second centrifugation, and the solid portion is dispersed in water, ultrasonicated, subjected to a third centrifugation, and freeze-dried;
[0018] The intercalant comprises at least one of dihydrolevorotatory glucosone, dimethyl sulfoxide, N,N-dimethylformamide, acetone, n-hexane and ethanol.
[0019] In some embodiments, the mass ratio of the dried solid phase to the intercalant is 1:(20-30).
[0020] In some embodiments, the shear peeling conditions include: a shearing speed of 4000-8000 rpm and a shearing time of 4-10 h.
[0021] In some embodiments, the conditions of the first centrifugation are: centrifugation at 2500-4000 rpm for 4-10 min;
[0022] and / or the second centrifugation condition is: centrifugation at 8000-15000 rpm for 20-60 min;
[0023] And / or the condition of the third centrifugation is: centrifugation at 3000-5000 rpm for 40-80 min.
[0024] The second aspect of the present application provides the use of the aforementioned Fenton-like catalytic system in the degradation of acetaminophen.
[0025] The third aspect of the present application provides a method for degrading acetaminophen, which uses the aforementioned Fenton-like catalytic system to treat a material to be treated containing acetaminophen.
[0026] The fourth aspect of the present application provides a method for removing acetaminophenol in water, comprising the following steps:
[0027] The aforementioned MXene is added to wastewater containing acetylaminophenol, H2O2 is added, and a visible light source is added or not to carry out a reaction.
[0028] In some embodiments, the mass ratio of the MXene to the wastewater containing acetylaminophenol is 1:(5-20);
[0029] And / or the amount of H2O2 added to the wastewater containing acetylaminophenol is 5-20mM;
[0030] and / or the pH of the wastewater containing acetylaminophenol is 3-11;
[0031] And / or the power of the visible light source is 200-1000W.
[0032] Beneficial effects of this application:
[0033] 1. The Fenton-like catalytic system of the present application uses MXene with nanometer-level thickness and submicron or micron-level lateral dimensions as a catalyst, coupled with H2O2, with a larger specific surface area and reaction sites, and can give full play to the Fenton-like catalytic reaction of highly oxygen-philic single vacancies or vacancy cluster defects left in the etching reaction of H2O2 and MXene, accelerate the defect sites to form oxidized clusters through hydrolysis or extraction of oxygen, and is beneficial to the Fenton-like catalytic reaction of H2O2.
[0034] 2. The Fenton-like catalytic system of the present application can effectively utilize visible light in sunlight, is green and efficient, has the advantages of high H2O2 utilization rate, wide pH application range, low energy consumption, and low cost. It can achieve effective degradation of acetaminophen in the presence or absence of light, and meet the treatment requirements of wastewater containing acetaminophen.
[0035] 3. The Fenton-like catalytic system of the present application has a strong visible light absorption and conversion capability and a high removal rate of ACTP. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art description. The drawings are only used to illustrate the preferred implementation methods and are not considered to be limitations of the present application. The same reference symbols are used throughout the drawings to represent the same components. In the drawings:
[0037] Figure 1 Ti3C2T of Example 1-2 x SEM images; wherein (a) is a single-layer Ti3C2T x , (b) is the multilayer Ti3C2T of Example 1 x .
[0038] Figure 2 Ti3C2T of Example 1-2 x AFM images; (a) is a single-layer Ti3C2T x , (b) is the multilayer Ti3C2T of Example 1 x .
[0039] Figure 3 Ti3C2T of Example 1-2 x Tyndall effect diagram; wherein (a) is a single-layer Ti3C2T x , (b) is the multilayer Ti3C2T of Example 1 x .
[0040] Figure 4 The degradation curves of ACTP in different systems; USM is the single-layer Ti3C2T x ; MLM is the multilayer Ti3C2T of Example 1 x .
[0041] Figure 5 Ti3C2T x Effect curve of addition amount and H2O2 content on degradation performance of ACTP; USM is the single-layer Ti3C2T x ; MLM is the multilayer Ti3C2T of Example 1 x .
[0042] Figure 6 is the effect curve of pH on the degradation performance of ACTP; wherein USM is the single-layer Ti3C2T x ; MLM is the multilayer Ti3C2T of Example 1 x . DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solution and advantages of this application clearer and to provide a more thorough and comprehensive understanding of the disclosed content of this application, the technical solution of this application will be clearly and completely described below in conjunction with the specific embodiments of this application and the corresponding drawings. The described embodiments are only part of the embodiments of this application, not all of them.
[0044] The implementation of the present application is described in detail below in conjunction with the accompanying drawings. This embodiment is implemented based on the technical solution of the present application, and a detailed implementation method and specific operation process are given, but the protection scope of the present application is not limited to the following embodiments.
[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0046] the term
[0047] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:
[0048] In the present application, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" or "at least one" means one or greater than or equal to two.
[0049] In the present application, the terms "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.
[0050] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0051] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum value and the maximum value) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers in the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints, which is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical range disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows broadly including numerical interval types such as percentage intervals, ratio intervals, and ratio intervals.
[0052] In the present application, the term "room temperature" generally refers to 4-35° C., preferably 20±5° C. In the embodiments of the present application, room temperature refers to 20-30° C.
[0053] In this application, unless otherwise specified, the temperature parameter is allowed to be either a constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C and ±1°C are allowed.
[0054] In this application, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 2-5h means that the units of the left endpoint "2" and the right endpoint "5" are both h (hours).
[0055] In a first aspect of the present application, a Fenton-like catalytic system is provided, comprising MXene and H2O2.
[0056] It can be understood that the MXene includes a single layer or a multilayer MXene.
[0057] Photo-Fenton catalytic technology mainly utilizes photochemical reactions and Fenton reactions to degrade and remove pollutants. In the reaction, photocatalysts are used to absorb light-excited electrons to produce active species to promote the photo-Fenton reaction. This can make full use of green solar energy, avoid the generation of sludge, and achieve efficient circulation of H2O2.
[0058] As a new type of two-dimensional transition metal carbide and carbonitride, MXene has excellent physical, chemical and thermal properties, with multiple functional groups, large specific surface area, excellent electronic conductivity and abundant exposed metal sites. In particular, in the preparation of MXene, in the process of etching to remove the Al layer of the MAX phase material, transition metal atoms are occasionally stripped, leaving highly oxygen-philic single vacancies or vacancy cluster defects. These defect sites are easy to form oxidized clusters by hydrolysis or extraction of oxygen, which is conducive to Fenton-like catalytic reaction with H2O2, and has strong visible light absorption and conversion ability. Under visible light conditions, it can make full use of green solar energy to achieve a more effective removal effect on ACTP.
[0059] The MXene nanosheets prepared by the general method are smaller in size and have fewer reaction sites. In comparison, the present application uses MXene with nanometer-level thickness and submicron or micron-level lateral dimensions as a catalyst, coupled with H2O2, with a larger specific surface area and reaction sites, and can give full play to the Fenton-like catalytic reaction of highly oxygen-philic single vacancies or vacancy cluster defects left in the etching reaction of H2O2 and MXene, accelerate the defect sites to form oxidized clusters through hydrolysis or extraction of oxygen, and is conducive to the Fenton-like catalytic reaction of H2O2. Specifically, the average thickness of MXene can be 1-500nm, and the average lateral dimension can be 0.3-12μm.
[0060] In some embodiments, the chemical formula of the MXene is M n+1 X n T x ; wherein n=1-3, M is selected from Ti, V, Mo, Sc, Zr, W, Cr, Ta, Nb or Hf; X is C or N; T x Selected from -OH, -F, -Cl or -O.
[0061] In some embodiments, the MXene is Ti3C2T x ; The Ti3C2T x The preparation method comprises:
[0062] Mixing lithium fluoride with the first hydrochloric acid solution to prepare a mixed solution;
[0063] The MAX phase material is added to the mixed solution, an etching reaction is performed, a first centrifugation is performed, the solid phase is washed with a second hydrochloric acid solution, and dried to prepare the Ti3C2T x .
[0064] It is understandable that there is no special requirement for the specific type of MAX phase material. In some embodiments, in the MAX phase material, M is selected from Ti, V, Mo, Sc, Zr, W, Cr, Ta, Nb or Hf, X is C or N, and A is Al or Si. The MAX phase material can be a commercially available product or can be prepared by itself.
[0065] Optionally, the molar concentration of the first hydrochloric acid solution is 6-12 mol / L, specifically 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L, 11 mol / L, 12 mol / L, etc.; the mass volume ratio of the lithium fluoride to the first hydrochloric acid solution is 1 g: (10-30) mL, specifically 1 g: 10 mL, 1 g: 15 mL, 1 g: 20 mL, 1 g: 25 mL, 1 g: 30 mL, etc.; the mass ratio of the MAX phase material to the lithium fluoride is (0.3-1): 1, specifically 0.3: 1, 0.4: 1, 0.5: 1, 0.6: 1, 0.7: 1, 0.8: 1, 0.9: 1, 1: 1, etc.; the molar concentration of the second hydrochloric acid solution is 1-3 mol / L, specifically 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, etc.
[0066] Optionally, the conditions for mixing lithium fluoride with the first hydrochloric acid solution include: stirring at a speed of 300-800 rpm for 60-90 min, and the stirring speed can specifically be 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm; the stirring time can specifically be 60 min, 70 min, 80 min, 90 min, etc.; the conditions for the etching reaction include: reacting at 25-40°C for 24-72h, specifically, reacting at 25°C, 30°C, 35°C or 40°C for 24h, 30h, 36h, 42h, 48h, 54h, 60h, 66h or 72h.
[0067] In some embodiments, the drying step further includes an intercalation stripping step; the intercalation stripping step includes:
[0068] The dried solid phase is dispersed in the intercalant, sheared and stripped, and subjected to a second centrifugation, and the solid portion is dispersed in water, ultrasonicated, subjected to a third centrifugation, and freeze-dried;
[0069] The intercalant comprises at least one of dihydrolevorotatory glucosone, dimethyl sulfoxide, N,N-dimethylformamide, acetone, n-hexane and ethanol.
[0070] It is understandable that after the intercalation and exfoliation steps, multilayer MXene can be exfoliated into a single-layer MXene, and a single-layer MXene has more reaction sites than a multilayer MXene. Among them, the intercalation agent dihydro-levorotatory glucosyl ketone, as a green solvent and chemical raw material, contains functional groups such as hydroxyl and carbonyl, which can interact with the functional groups on the surface of MXene to achieve intercalation and exfoliation to obtain a single-layer MXene.
[0071] In some embodiments, the mass ratio of the dried solid phase to the intercalant is 1:(20-30), specifically 1:20, 1:22, 1:24, 1:26, 1:28, 1:30, etc.
[0072] In some embodiments, the shear peeling conditions include: a shear speed of 4000-8000rpm, and a shear time of 4-10h; specifically, the shear speed can be 4000rpm, 5000rpm, 6000rpm, 7000rpm, 8000rpm, etc.; the shear time can be 4h, 5h, 6h, 7h, 8h, 9h, 10h, etc.
[0073] Optionally, the first centrifugation condition is: centrifugation at 2500-4000 rpm for 4-10 min, specifically centrifugation at 2500 rpm, 3000 rpm, 3500 rpm or 4000 rpm for 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min; the second centrifugation condition is: centrifugation at 8000-15000 rpm for 20-60 min, specifically centrifugation at 8000 rpm, 9000 rpm, 10000 rpm, 11000 rpm, 12000 rpm, 14000 rpm, 15000 rpm, 16000 rpm, 17000 rpm, 18000 rpm, 19000 rpm, 20000 rpm, 210000 rpm, 220000 rpm, 230000 rpm, 24000 rpm, 25000 rpm, 30000 rpm, 35000 rpm or 4000 rpm The conditions of the third centrifugation are: centrifugation at 3000-5000 rpm for 40-80 min, specifically centrifugation at 3000 rpm, 3500 rpm, 4000 rpm, 4500 rpm or 5000 rpm for 40 min, 50 min, 60 min, 70 min or 80 min.
[0074] The second aspect of the present application provides the use of the aforementioned Fenton-like catalytic system in the degradation of acetaminophen.
[0075] The third aspect of the present application provides a method for degrading acetaminophen, which uses the aforementioned Fenton-like catalytic system to treat a material to be treated containing acetaminophen.
[0076] It can be understood that the acetaminophen-containing material to be treated includes wastewater containing acetaminophen.
[0077] The fourth aspect of the present application provides a method for removing acetaminophenol in water, comprising the following steps:
[0078] The aforementioned MXene is added to wastewater containing acetylaminophenol, H2O2 is added, and a visible light source is added or not to carry out a reaction.
[0079] Optionally, the mass ratio of the MXene to the wastewater containing acetaminophenol is 1:(5-20), specifically 1:5, 1:10, 1:15, 1:20, etc.; the amount of H2O2 added to the wastewater containing acetaminophenol is 5-20mM, specifically 5mM, 10mM, 15mM, 20mM, etc.; the pH of the wastewater containing acetaminophenol is 3-11, specifically 3, 4, 5, 6, 7, 8, 9, 10, 11, etc., preferably, the pH is 3-7; the power of the visible light source is 200-1000W, specifically 200W, 300W, 400W, 500W, 600W, 700W, 800W, 900W or 1000W.
[0080] Unless otherwise specified, the raw materials used in the following experiments can be purchased from the market. The following is an exemplary description of some of the raw materials used in the examples:
[0081] MAX phase material: Ti3AlC2, purchased from McLean Company.
[0082] The following are specific embodiments.
[0083] Example 1
[0084] Multilayer Ti3C2T x The specific steps of (MXene) are:
[0085] 1) Sieve the MAX phase material to a particle size of ≤200 mesh;
[0086] 2) Prepare 9M hydrochloric acid solution and 2M hydrochloric acid solution;
[0087] 3) Add 2.5 g of lithium fluoride to 50 mL of 9 M hydrochloric acid solution and stir continuously at 500 rpm for 1 h to allow the reaction to be uniform to obtain a mixed solution;
[0088] 4) Slowly add 1.25 g of MAX material that meets the requirements to the mixed solution in step 3) to avoid boiling and splashing of the solution;
[0089] 5) placing the solution obtained in step 4) in a water bath at 40° C. for 48 h to perform etching reaction;
[0090] The solution of step (5) after the etching reaction was centrifuged at 3500 rpm for 5 minutes, the supernatant was discarded, and the mixture was washed several times with the 2M hydrochloric acid solution of step 2), the supernatant was discarded, and the mixture was washed several times with water until the pH value was ≥ 6. The precipitate was collected and dried in a vacuum drying oven at 60 °C for 24 h to obtain a multilayer Ti3C2T x (MXene), denoted as MLM.
[0091] The obtained multilayer Ti3C2T x The SEM and AFM morphology and Tyndall effect of (MXene) are shown in the figure. Figure 1-3 shown.
[0092] Example 2
[0093] Single layer Ti3C2T x The specific steps of (MXene) are:
[0094] 1) The multilayer Ti3C2T prepared in Example 1 x (MXene) was added to dihydro-levulinic acid ketone at a solid-liquid ratio of 1:25 (mass ratio) to obtain a uniform dispersion;
[0095] 2) Exfoliate the homogenized dispersion from step 1) using a high shear mixer (Silverson L5M) at 6000 rpm for 6 hours at room temperature (using an ice bath to absorb excess heat generated during the process);
[0096] 3) The black dispersion obtained after exfoliation in step 2) was centrifuged at 10000 rpm for 30 minutes, and the upper intercalation liquid was discarded to obtain the exfoliated few layers and the unexfoliated flakes; the exfoliated few layers and the unexfoliated Ti3C2T x The (MXene) flakes were redispersed in pure water and subjected to ice bath ultrasonication for 2 h in a N2 atmosphere to completely exfoliate into single-layer Ti3C2T x (MXene), the resulting solution was centrifuged at 4000 rpm for 60 min in a centrifuge, and the supernatant was collected;
[0097] 4) To avoid the drying of the prepared single-layer Ti3C2T x The (MXene) flakes were stacked to maintain the morphology and form in the solution to the greatest extent possible, and then dried in a freeze dryer at -45 to -50 °C for 24 h to obtain a single layer of Ti3C2T x (MXene), denoted as USM.
[0098] The obtained single-layer Ti3C2T x The SEM and AFM morphology and Tyndall effect of (MXene) are shown in the figure. Figure 1-3 shown.
[0099] Example 3
[0100] The single-layer and multi-layer Ti3C2T prepared in Example 1 and Example 2 were used respectively. x (MXene) was used as a catalyst, coupled with H2O2 and / or light to provide a Fenton-like reaction system, and its degradation performance for wastewater containing acetylaminophenol was studied.
[0101] The simulated wastewater with an initial concentration of 5 mg / L ACTP solution was prepared to study the x , H2O2 and light on the degradation effect of ACTP, wherein the Ti3C2T x Add H2O2 at a solid-liquid ratio of 1:5 (mass ratio), with an amount of 15mM, and react for 1h in the absence of light or with a 350W visible light source.
[0102] The pH value of the simulated phosphorus-containing wastewater was around 5.7 before the experiment, and around 5 after the experiment.
[0103] After the experiment, the concentration of ACTP was measured and the removal rate was calculated.
[0104] Removal rate calculation formula: Formula (1);
[0105] In formula (1), ŋ is the removal rate (%); C0, C e are the initial phosphorus concentration before treatment and the phosphorus concentration after treatment (mg / L), respectively.
[0106] The experimental results are as follows Figure 4 As shown in the figure, A represents the degradation effect of ACTP when only H2O2 is added; B represents the degradation effect of ACTP when only light is irradiated; C represents the degradation effect of ACTP when only H2O2 and light are added; D represents the degradation effect of ACTP when only a single layer of Ti3C2T is added x Degradation effect of ACTP when (MXene) (USM) and H2O2 are added; E represents the addition of multilayer Ti3C2T x Degradation effect of ACTP on (MXene)(MLM) and H2O2; F represents single-layer Ti3C2T x Degradation effect of ACTP by photocatalytic Fenton-like system of (MXene)(USM) coupled with H2O2 and light; G represents multilayer Ti3C2T x Degradation effect of ACTP on the photocatalytic Fenton-like system of (MXene)(MLM) coupled with H2O2 and light.
[0107] from Figure 4It can be seen that when using H2O2 or light alone, ACTP is almost not degraded. When light is coupled with H2O2, single or multi-layer Ti3C2T x Coupling with H2O2 can significantly improve the degradation efficiency of ACTP; under light, single or multi-layer Ti3C2T x Coupling with H2O2 can greatly improve the degradation efficiency of ACTP, and the removal rate can reach 100% in 60 minutes. x It can be used as a catalyst to couple H2O2, which is beneficial to the Fenton-like catalytic reaction of H2O2 under light or no light conditions, thereby improving the degradation efficiency of ACTP.
[0108] Example 4
[0109] The single-layer and multi-layer Ti3C2T prepared in Example 1 and Example 2 were used respectively. x (MXene) is used as a catalyst, coupled with H2O2 and light to provide a photocatalytic Fenton reaction system, and the performance evaluation of degrading acetaminophenol wastewater is explored when the optimal catalyst addition amount and the optimal H2O2 content are used.
[0110] Prepare simulated wastewater with an initial concentration of 5 mg / L ACTP solution, add the materials prepared in Examples 1 and 2 respectively, add 5, 10, 15, 20, 25, and 30 mg of the catalyst (100 mL of simulated wastewater), add 0, 5, 10, 15, and 20 mM H2O2, turn on a 350 W visible light source, and react for 1 h.
[0111] After the experiment, the concentration of ACTP was measured and the removal rate was calculated.
[0112] The experimental results are as follows Figure 5 As shown in the figure, it can be seen that as the amount of catalyst and H2O2 increases, the removal rate of ACTP increases accordingly. x and the single-layer Ti3C2T of Example 2 x For example, when the amount of catalyst added reaches 20 mg and the concentration of H2O2 reaches 15 mM, the removal rate of ACTP can reach 100%.
[0113] Example 5
[0114] The single-layer and multi-layer Ti3C2T prepared in Example 1 and Example 2 were used respectively. x (MXene) is used as a catalyst, coupled with H2O2 and light to provide a photocatalytic Fenton reaction system, and the effects of the pH of the initial ACTP solution and other conditions on the degradation performance of ACTP wastewater are evaluated.
[0115] Prepare simulated wastewater with an initial concentration of 5 mg / L ACTP solution (adjust the pH to 3, 5, 7, 9, 11), add the materials prepared in Examples 1 and 2 respectively, add 15 mM H2O2 at a solid-liquid ratio of 1:5, turn on a 350 W visible light source, and react for 1 h.
[0116] The experimental results are as follows Figure 6 As shown, it can be seen that the photocatalytic Fenton reaction system corresponding to Examples 1-2 has a certain removal effect under the condition of pH 3-11, among which the removal rate under alkaline conditions is lower than that under acidic and neutral conditions, and the treatment effect is optimal when the initial pH of the ACTP solution is 5.
[0117] Example 6
[0118] The single-layer and multi-layer Ti3C2T prepared in Example 1 and Example 2 were used respectively. x (MXene) is used as a catalyst, coupled with H2O2 and light to provide a photocatalytic Fenton reaction system to explore the processing efficiency of reuse.
[0119] Prepare simulated wastewater with an initial concentration of 5 mg / L ACTP solution, and add the Ti3C2T x Add H2O2 at a solid-liquid ratio of 1:5 (mass ratio), the amount of H2O2 is 15mM, turn on the 350W visible light source, and react for 1h. After the reaction is completed, centrifuge and separate the Ti3C2T x The mixture was freeze-dried and ground at -50°C, and then subjected to ACTP degradation treatment again according to the above conditions. The results are shown in Table 1.
[0120] Table 1 Repeated treatment efficiency of photocatalytic Fenton reaction system
[0121]
[0122] It can be seen from Table 1 that the Ti3C2T x After repeated use for five times, the removal rates of ATCP can reach 69.7% and 62.1% respectively. x It can be reused and has good stability.
[0123] In summary, the Ti3C2T x Coupling H2O2, or coupling H2O2 and light at the same time, can effectively remove ATCP and has good reusability. x Compared with the single-layer Ti3C2T xIt has comparable performance in degrading ATCP and better reusability. It can be seen that when using MXene with nanometer-level thickness and submicron or micron-level lateral dimensions as a Fenton-like catalyst, using multilayer MXene with a simpler preparation process can achieve technical effects comparable to or even better than single-layer MXene.
[0124] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0125] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A Fenton-like catalytic system, characterized in that: Including MXene and H2O2.
2. The Fenton-like catalytic system according to claim 1, characterized in that: The chemical formula of the MXene is M n+1 X n T x ; wherein n=1-3, M is selected from Ti, V, Mo, Sc, Zr, W, Cr, Ta, Nb or Hf; X is C or N; T x Selected from -OH, -F, -Cl or -O.
3. The Fenton-like catalytic system according to claim 1 or 2, characterized in that: The MXene is Ti3C2T x ; Optionally, the Ti3C2T x The preparation method comprises: Mixing lithium fluoride with the first hydrochloric acid solution to prepare a mixed solution; The MAX phase material is added to the mixed solution, an etching reaction is performed, a first centrifugation is performed, the solid phase is washed with a second hydrochloric acid solution, and dried to prepare the Ti3C2T x .
4. The Fenton-like catalytic system according to claim 3, characterized in that: The molar concentration of the first hydrochloric acid solution is 6-12 mol / L; and / or the mass volume ratio of the lithium fluoride to the first hydrochloric acid solution is 1 g: (10-30) mL; and / or the mass ratio of the MAX phase material to the lithium fluoride is (0.3-1):1; and / or the molar concentration of the second hydrochloric acid solution is 1-3 mol / L; and / or the conditions for mixing the lithium fluoride with the first hydrochloric acid solution include: stirring at a rotation speed of 300-800 rpm for 60-90 min; And / or the etching reaction conditions include: 25-40° C. reaction time 24-72 hours.
5. The Fenton-like catalytic system according to claim 3, characterized in that: The drying step also includes an intercalation peeling step; The intercalation stripping step comprises: The dried solid phase is dispersed in the intercalant, sheared and stripped, and subjected to a second centrifugation, and the solid portion is dispersed in water, ultrasonicated, subjected to a third centrifugation, and freeze-dried; The intercalant comprises at least one of dihydrolevorotatory glucosone, dimethyl sulfoxide, N,N-dimethylformamide, acetone, n-hexane and ethanol.
6. The Fenton-like catalytic system according to claim 5, characterized in that: The mass ratio of the dried solid phase to the intercalant is 1:(20-30); And / or the shear peeling conditions include: shearing speed of 4000-8000rpm, shearing time of 4-10h; and / or the first centrifugation condition is: centrifugation at 2500-4000 rpm for 4-10 min; and / or the second centrifugation condition is: centrifugation at 8000-15000 rpm for 20-60 min; And / or the condition of the third centrifugation is: centrifugation at 3000-5000 rpm for 40-80 min.
7. Use of the Fenton-like catalytic system as described in any one of claims 1 to 6 in the degradation of acetaminophen.
8. A method for degrading acetaminophen, characterized in that: Using the Fenton-like catalytic system as described in any one of claims 1 to 6 to treat a substance to be treated containing acetaminophen; Optionally, the acetaminophen-containing material to be treated includes wastewater containing acetaminophen.
9. A method for removing acetaminophen from water, characterized in that: The steps include: The MXene described in any one of claims 1 to 6 is added to wastewater containing acetylaminophenol, H2O2 is added, and a visible light source is added or not added to carry out a reaction.
10. The method according to claim 9, characterized in that The mass ratio of the MXene to the wastewater containing acetylaminophenol is 1:(5-20); And / or the amount of H2O2 added to the wastewater containing acetylaminophenol is 5-20mM; and / or the pH of the wastewater containing acetylaminophenol is 3-11; And / or the power of the visible light source is 200-1000W.
Citation Information
Patent Citations
Preparation method and application of supported transition metal carbide Fenton-like nano-catalyst
CN111715250A
Method for oxidative degradation of heavy metal complex and recovery of heavy metal through MXene reinforced Fenton
CN113087117A
Metal oxide nanosheet material, preparation method thereof and lithium ion battery
CN114388760A
MXene nano-material as well as preparation method and application thereof
CN116730342A
MXene quantum dot as well as high-yield preparation method and application thereof
CN117865157A
Cited By
Persulfate advanced oxidation system, application of persulfate advanced oxidation system in degradation of acetaminophen and application method of persulfate advanced oxidation system
CN120838447A
A persulfate advanced oxidation system and its application and application method in degrading acetaminophen
CN120838447B